The role of novel protein-protein interactions in the function and mechanism of the sarcomeric protein, myosin binding protein H (MyBPH) - Mouton, Jacoba Martina (Stellenbosch : Stellenbosch University, 2014)
Thesis (PhD)--Stellenbosch University, 2014.